Properties of jet and surrounding material of GW/GRB 170817A. Issue 2 (3rd October 2019) - Ziaeepour, Houri
ABSTRACT: We use published data in radio, optical, and X-ray bands to analyse and model afterglows of GW/GRB 170817A. Our analysis is based on a phenomenological gamma-ray burst generator model, which we previously used to study the prompt gamma-ray emission of this important transient. We find a multicomponent model and a few of its variants that are consistent with broad-band ∼1 yr observations of afterglows, once the contribution of kilonova in optical/IR band is taken into account. Considering beaming and off-axis view of relativistic outflows, we interpret the components of the model as approximately presenting the profile of a relativistic structured jet with a rapidly declining Lorentz factor from our line of sight, where it had a Lorentz factor of O(100), to outer boundaries, where it became a mildly relativistic cocoon with a relative velocity to light of ∼0.4–0.97. Properties of the ultra-relativistic core of the jet obtained here are consistent with conclusions from analysis of the prompt gamma-ray emission. In particular, our results show that after prompt internal shocks the remnant of the jet retained in some extent its internal collimation and coherence. Slow rise of the afterglows can be associated to low density of circumburst material and low column density of the jet. The long distance of external shocks from the merger, which could have been in part responsible for extensive thinning of the jet through expansion and energy dissipation before occurrence of external shocks, is responsible for the peak of emission being at ≳110 d after the merger. We discuss implications of these observations for origin and properties of circumburst material around binary neutron stars. This analysis confirms our previous results showing that an outflow with a Lorentz factor of ∼2–5 cannot explain observed afterglows without an additional X-ray source or significant absorption of optical/IR photons.